Directional Clustering of Slanted Nanopillars by Elastocapillarity. Issue 28 (7th June 2016) - Kim, Sang Moon; Kim, Junsoo; Kang, Seong Min; Jang, Segeun; Kang, Daeshik; Moon, Seung Eon; Kim, Hong Nam; Yoon, Hyunsik
Abstract : The unidirectional clustering induced by capillary force of drying liquids between pillars is investigated and a theoretical model to set a criterion of the unidirectional clustering of the slanted nanopillars is proposed.